Analisis Pengaruh Pertumbuhan Ekonomi, Rasio Beban Ketergantungan Penduduk dan IPM TerhadapKetimpangan Pendapatan di SumbagselPerspektif Ekonomi Islam - Setiawan, Aris; iqbal, Muhammad; Nuraziza, Sania (ILTIZAM Journal of Shariah Economics Research, 2025)
From an Islamic economics vantage point, this research intends to examine the impact of population dependence ratio, economic development, and the Human Development Index (HDI) on income disparity in Sumbagsel, a region in southern Sumatra.  Panel data from six Sumbagsel provinces spanning 2015–2024 form the basis of this study.  The data was analyzed with the help of EViews 12.  Income inequality is positively and significantly affected by the dependence ratio, and negatively and significantly by the HDI, according to the data.  At the same time, there is no discernible impact from economic expansion.  With a combined F-statistic likelihood value of 0.0000, all three factors were determined to significantly impact income inequality. These findings suggest that improving the quality of human development can help reduce inequality, whereas a high dependency ratio tends to widen it. From the Islamic economic perspective, equitable development through the enhancement of human resources and fair distribution is a core principle in promoting just and sustainable growth. Keywords: Income Inequality, Economic Growth, Dependency Ratio, HDI, Islamic Economics